The development of comic-based teaching material using contextual approach to students of amalyatul huda elementary school medan - Rani Rahim; Suhariyanti Suhariyanti; M. Arif Rahman (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2022)
This study aims to determine how the development of comic-based teaching material using a proper and effective contextual approach. The teaching material developed is comic-based teaching material using a contextual approach. The subjects in this study were fourth-grade students of SD Amalyatul Huda Medan. This type of research is R & D research using the 4-D model. To see the feasibility of teaching material is obtained from 5 validation experts. Meanwhile, to see the effectiveness of teaching materials obtained from trials of teaching material. The trial was carried out twice. The first trial was conducted on nine students consisting of three students in low ability,three students in medium ability, and three students in high ability. While the second trial was conducted on fourth-grade students consisting of 32 students. Based on the conclusions from five experts, they stated that comic-based teaching material using contextual approach were included in the good category and deserved to be used. Meanwhile, based on student assessment result of the teaching material in the first and second trials, the category was excellent. It can be concluded that the development of comic-based teaching material using contextual approach is feasible and effective for students.